RESOURCE POLICY OF BANKS WITH FOREIGN CAPITAL IN UKRAINE: PECULIARITIES AND PRIORITIES - Rysin, Vitaliy (Ekonomika, 2014)
Abstract. The goal of the research was to reveal the characteristic features of resource policy in banks with foreign capital during the period of the Ukrainian banking sector post-crisis recovery. Modern changes of the banking system’s structure are described. The reasons for foreign capital outflow and foreign banks’ withdrawal from the market are identified. The peculiarities and distinctions of resource policy implementation by Ukrainian and foreign banks are investigated. Changes of resource policy riskiness in the post-crisis period are estimated by using the loan-to-deposit ratio. The mechanisms of risk reduction are recommended. Key words: bank, resource policy, deposit, loan, foreign capital